Enhancing digital academic services through Academic Information System quality: Insights from Universitas Methodist Indonesia - Lestari Natalia Br Sianipar; Darwis Robinson Manalu (Eduvista: Journal of Education and Innovation, 2026)
Digital transformation has increased the strategic role of Academic Information Systems (AIS) in supporting academic services in higher education. However, empirical evidence regarding which quality dimensions most strongly influence User Satisfaction in digital academic services remains inconclusive. This study aims to examine the effects of System Quality, Information Quality, and Service Quality on User Satisfaction with the Academic Information System at Universitas Methodist Indonesia. A quantitative survey was conducted involving 100 undergraduate students selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics. The findings reveal that Information Quality and Service Quality have positive and significant effects on User Satisfaction, whereas System Quality has no significant effect. The proposed model explains 67.9% of the variance in User Satisfaction (R² = 0.679). These findings suggest that improving digital academic services in higher education should prioritize high-quality academic information and responsive support services to enhance user experience and satisfaction. Abstrak Transformasi digital telah mendorong perguruan tinggi untuk mengoptimalkan Sistem Informasi Akademik (SIMAK) sebagai pendukung layanan akademik. Namun, bukti empiris mengenai dimensi kualitas yang paling berpengaruh terhadap kepuasan pengguna dalam mendukung layanan akademik digital masih menunjukkan hasil yang beragam. Penelitian ini bertujuan menganalisis pengaruh System Quality, Information Quality, dan Service Quality terhadap User Satisfaction pada penggunaan SIMAK di Universitas Methodist Indonesia. Penelitian menggunakan pendekatan kuantitatif dengan metode survei terhadap 100 mahasiswa yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis menggunakan regresi linear berganda dengan IBM SPSS Statistics. Hasil penelitian menunjukkan bahwa Information Quality dan Service Quality berpengaruh positif dan signifikan terhadap kepuasan pengguna, sedangkan System Quality tidak berpengaruh signifikan. Model penelitian mampu menjelaskan 67,9% variasi kepuasan pengguna (R² = 0,679). Temuan ini menegaskan bahwa peningkatan layanan akademik digital di perguruan tinggi perlu diprioritaskan pada penyediaan informasi akademik yang berkualitas dan layanan yang responsif sehingga mampu meningkatkan pengalaman belajar dan kepuasan pengguna.